ANALISIS PENERAPAN SISTEM E-KINERJA PADA BADAN NARKOTIKA NASIONAL KABUPATEN KARAWANG - Vicka Riri Puspita; Budi Rismayadi; Wike Pertiwi (Universitas Sarjanawiyata Tamansiswa, 2026)
The aim of this research is analyze the implementation of the E-Kinerja System at the National Narcotics Agency of Karawang Regency and to identify constraints in the process of employee performance assessment and reporting. This study used a descriptive qualitative approach. The population of this research consisted of all employees of BNNK Karawang who use the E-Kinerja system. Informants were selected through purposive sampling, involving five informants: the Head of the General Subdivision as the main informant, administrative staff as key informants, and employees from the P2M Section, Rehabilitation Section, and Eradication Section as supporting informants. Data were collected through in-depth interviews also observation. Data validity was ensured through source triangulation by comparing information from various informants. The results indicate that the implementation of the E-Kinerja System at BNNK Karawang has generally been well implemented and facilitates employees in recording targets, performance realization, and performance reporting in a structured and well-documented manner. However, its implementation has not been fully optimal due to technical constraints, particularly system disruptions and limited server capacity. Simultaneous system access by BNN civil servants across Indonesia during limited reporting periods often causes system delays or errors, affecting the timeliness of performance reporting. Therefore, technical improvements are needed to optimize the implementation of the E-Kinerja System.